STUDI KINERJA RUAS JALAN DAN SIMPANG SEKITAR BENGKEL TOKO PERKASA RAJA MOTOR KOTA KOTAMOBAGU: Ahmadil Fitrah - Ahmadil Fitrah (Jurnal Karajata Engineering, 2022)
Abstract Toko Perkasa Raja Motor is a type of activity center in the form of a building intended for motorized vehicle workshops located on the Molinow Urban Village, Kotamobagu Barat District, Kotamobagu City with a building floor area of 640 m2, which will develop in front of the current location with a land area of 374 m2. With this development it is estimated that it has an influence on the surrounding traffic, so an analysis of the performance of roads and intersections is carried out to determine traffic volume and identify changes in road and intersection service levels due to development impacts. The results of the analysis show that the highest traffic volume occurs on Thursday 4 February 2021, peak hours at 10.00-11.00 WITA with a total vehicle of 244 vehicles / hour or 129.10 pcu / hour and the lowest is 72.20 pcu / hour at 17.00-18.00 WITA. The level of service in segment 1 Jalan Kampus has a V/C ratio of 0.04 or LoS A, at segment 2 intersection 3 Jalan Kampus-Jalan Rawa Mangun, the value of V/C ratio is 0.07 or LoS A, at segment 3 intersection 4 Jalan Kampus-Jalan Amal-Jalan Adampe Dolot has a V/C ratio value of 0.18 or LoS A.